Cellulose and starch-based bioplastics: a review of advances and challenges for sustainability - Hossain, Md. Tanvir; Shahid, Md. Abdus; Akter, Sinthia; Ferdous, Jannatul; Afroz, Khadija; Refat, Kazi Refatul Islam; Faruk, Omor; Jamal, Mohammad Salman Ibna; Uddin, Md Nur; Samad, Md. Abdullah Bin (Polymer-plastics technology and engineering, 2024)
In recent years, bioplastics have been making great strides in a promising way toward mitigating the damage that traditional plastics cause to the environment. This article discusses the status of cellulose and starch-based bioplastics in detail. To provide readers with helpful information, a variety of processes are analyzed, including polymerization, injection molding, film casting, 3D printing solvent-free methods, and electrospinning, along with prospects and challenges. This research also examines the numerous applications of bioplastics, including medical equipment, food packaging, textiles, and healthcare appliances with sustainable innovative concepts. In the end, the paper highlights a future outlook.